(E)-2-Furyl methyl ketone 2,4-dinitrophenylhydrazone - Shan, Shang (International Union of Crystallography, 2008)
Crystals of the title compound, C(12)H(10)N(4)O(5), were obtained from a condensation reaction of 2,4-dinitrophenylhydrazine and 2-furyl methyl ketone. The molecule displays a nearly planar structure, and the furan ring is slightly twisted by a dihedral angle of 12.62 (6)° with respect to the phenylhydrazone plane. The face-to-face separation of 3.287 (7) Å between parallel benzene rings of adjacent molecules indicates the existence of π–π stacking between dinitrophenyl rings in the crystal structure.